(untitled) (La Rivada, 2024)
In this article we establish a dialogue between two artistic languages, literature and film. We address the novel Distancia de rescate by Samanta Schweblin (2017) and the film of the same name directed by Claudia Llosa (2021). The story, common to both works, takes place in the soy-growing region of la pampa, in a town that is sustained by an agricultural business model configured with financial strategies typical of late capitalism. We consider that both text and film operate in ways that produce in readers and viewers an effect of the order of the weird and the eerie (Fischer, 2018), condensing a type of horror in which we read the symptoms of the eerie entity that constitutes the capital in the areas of the pampas managed by an agro-capitalist model. From the analysis of three major axes on which we build our hypothesis: from the narrative towards the remains of an indexical paradigm, the body, the monstrous and the search for the exact point, we read the varied range of nuances that are put into play between one and another text of culture.